Resilience in university students from Arequipa: Psychometric analysis of the Wagnild and Young Resilience Scale and comparisons based on sex and age - Arias Gallegos, Walter L. (2024)
The present study has two objectives. On the one hand, the psychometric properties of the Wagnild and Young (1993) Resilience Scale are analyzed, and on the other hand, the values ​obtained were compared according to sex and age of the participants. The sample were 333 university students from a private university in Arequipa (Peru), of which approximately half were men and the other half women, with an average age of 17 years. The results of confirmatory factor analysis suggest a four-factor structure: Interest, Energy and strength, Purpose identity and Decision, with adequate goodness of fit indices. However, for the dimensions of Decision and Energy and strength, internal consistency had inadequate values. Comparative data indicate that women and 18-year-old students have higher scores on some resilience factors than men and 16-year-old students. Results suggest the need for extending psychometric research of this instrument in Peruvian population.